2023
DOI: 10.1039/d3cp02261g
|View full text |Cite
|
Sign up to set email alerts
|

How oxidized EGCG remodels α-synuclein fibrils into non-toxic aggregates: insights from computational simulations

Priscila Baltazar Gonçalves,
Fernando L. Palhano,
Yraima Cordeiro
et al.

Abstract: The misfolding and aggregation of the presynaptic protein α-synuclein (α-syn) is a pathological hallmark of Parkinson’s disease (PD). Targeting α-syn has emerged as a promising therapeutic strategy for PD. Emerging...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
(145 reference statements)
0
1
0
Order By: Relevance
“…(-)-epigallocatechin-3-gallate (EGCG) is the main molecule in green tea extracts with extensive biological activities [ 15 ]. Recent studies from computational simulations revealed that EGCG attenuates the α-syn protofibril-membrane interactions by forming interactions with the model membrane, thus restoring the membrane integrity, and that oxidized EGCG remodels the toxic α-syn fibrils into non-toxic aggregates by non-covalent interactions [ 16 , 17 ]. These results suggest that EGCG exerts neuroprotective effects, being potentially effective in delaying PD development.…”
Section: Introductionmentioning
confidence: 99%
“…(-)-epigallocatechin-3-gallate (EGCG) is the main molecule in green tea extracts with extensive biological activities [ 15 ]. Recent studies from computational simulations revealed that EGCG attenuates the α-syn protofibril-membrane interactions by forming interactions with the model membrane, thus restoring the membrane integrity, and that oxidized EGCG remodels the toxic α-syn fibrils into non-toxic aggregates by non-covalent interactions [ 16 , 17 ]. These results suggest that EGCG exerts neuroprotective effects, being potentially effective in delaying PD development.…”
Section: Introductionmentioning
confidence: 99%